Infection rates of MRSA in complicated pediatric rhinosinusitis: An up to date review. (January 2018) - Hamill, Chelsea S.; Sykes, Kevin J.; Harrison, Christopher J.; Weatherly, Robert A.
Abstract: Introduction: Published studies have reported a rise in MRSA isolates in head and neck infections, but the microbiology of complicated pediatric rhinosinusitis is unclear. One study of such patients showed that MRSA isolates were seen only in the last three years of data collection, suggesting a possible recent increased prevalence. Given the public health concerns of increasing rates of antimicrobial resistance, the goal of this study was to investigate the microbiologic patterns and outcomes of complicated pediatric rhinosinusitis. Methods: Retrospective cohort of pediatric patients admitted to our children's hospital with complicated acute rhinosinusitis from 2004 to 2014. Results: The mean age of 250 hospitalized children with complicated rhinosinusitis was 7.6 ± 4.9 years; 109 of these (43%) underwent surgical procedures. Although MRSA prevalence was highest in 2014, no significant trend in overall MRSA prevalence occurred when considering the entire study period. No significant relationship was identified between MRSA and intra-orbital versus intra-cranial complications. Interestingly, 22.7% of patients with anaerobes detected by culture had persistent abnormal physical examination (PE) findings versus 6.1% of patients without anaerobes (p = 0.025). Furthermore, multivariate analysis also revealed that detection of anaerobes or MRSA was associated with persistent PE findings being 21.8 and 14.8 times more likely, respectively, when compared to other detected pathogens. Discussion: Our data indicate modest variability in the annual rates of MRSA associated pediatric rhinosinusitis, however there was no statistically significant pattern of change in MRSA prevalence during 2004–2014. Although detection of MRSA was not significantly associated with either intraorbital or intracranial complications of sinusitis, a significant association with a poorer outcome was observed by multivariate analysis for patients from whom MRSA or anaerobes were detected. These data raise the question as to whether clindamycin is adequate for MRSA and anaerobic coverage.